A Study To Assess The Knowledge Regarding Rights And Responsibilities Among Patients Admitted To Tertiary Care Hospitals In Sangli, Miraj, And The Kupwad Corporation Area - Kulkarni, Manisha Sunil; Jogdeo, Bhagyashree; Ray, Suresh Kumar; Jadhav, Vaishali; Kale, Aparna; Kulkarni, Sunil Malhar (Journal of Neonatal Surgery, 2025)
Introduction: Patient rights are a code of conduct that governs interactions between patients and healthcare professionals. Assessing the knowledge of patients' rights and responsibilities have advantages and disadvantages. The title of study is “A study to assess the knowledge regarding rights and responsibilities among patients admitted in selected tertiary care hospitals in Sangli, Miraj, Kupwad Corporation area.” The objectives are 1.To assess the knowledge regarding rights of the patients. 2.To assess the knowledge regarding responsibilities of the patients.3.To find out the association of knowledge regarding rights and responsibilities with selected demographic variables. Methodology: A non-experimental descriptive research design was used and Quantitative approach was used for present study. By using simple random sampling technique 140 samples were selected for this study. A self-structured questionnaire was used to assess the knowledge score regarding rights and responsibilities among patients. A researcher gave the questionnaire to the patients for 15- 20 min to solve the questions. Analysis was done with using descriptive and inferential statistics and chi square test was used to find the association. Result and conclusion: The level of knowledge regarding Rights of patients showed that the patients 64(45.72%) had good knowledge, 52(37.14%) had average knowledge and 24(17.14%) had poor knowledge. The level of knowledge regarding Responsibilities of patients showed that the patients 76(54.28%) had good knowledge, 43(30.72%) had average knowledge and 21(15%) had poor knowledge. The association of knowledge regarding rights and responsibilities with selected demographic variables the P-value is less than 0.05 so there is significance association between the Age, Gender, Education, Duration of stay in hospital and Received information with knowledge regarding rights and responsibilities.